Physical Activity as A Major Low Back Pain Complaints Among Office Worker in Their Working Life: Cross Sectional Study - Rudi Hariyono; Arif Efendi; Rina Nur Hidayati (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Low back pain is a very common problem that can affect a variety of ages. The symptoms of low back pain can be caused by lumbar spine problems such as root pain, radiculopathy, and spinal tract stenosis. The intervertebral disk and the joint facet are two lumbar structures that can cause pain. One element that contributes to low back discomfort is physical activity. The study design used correlation analysis with a cross-sectional approach. The sampling technique used in this study is consecutive sampling. The sample is 37 teachers with an age range of 35 – 60 years. To indentify physical activity is used Short-Form International Physical Activity Questionnaire and for identifying low back pain complaints is used Pain and Distress Scale (William J.K. Zunga) in the Primala study was analyzed using the Chi-Square test. The teachers and perform moderate activities, don’t have complaints of low back pain of 15 (40,5%), heavy activity, did have a complaint of low back pain of 22 (59,5%). The results of the Chi-square test showed that there was a significant relationship between physical activity and low back pain complaints (p value=0,000;α<0,05). Appropriate and consistent activity that is adapted to the body's capacities and age will have a positive influence on the building of stronger muscles and bones. Adequate and regular physical activity can help prevent low back pain complaints